Predictors of Mortality in Newborn Admitted in Special Care Baby Unit (SCABU) of Dhaka Shishu Hospital (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: The current neonatal mortality rate of Bangladesh is very high compared to developed countries.Objective: The objective of the study was to find out the predictors that are associated with mortality in newborn admitted in Special Care Baby Unit (SCABU) of Dhaka Shishu (Children) Hospital.Methods: This prospective study was conducted in the SCABU of Dhaka Shishu (Children) Hospital from 1st June 2016 to 30 November 2016. A semi-structured questionnaire was prepared before the study. Data were collected from the attendents of each neonate by asking questions who died at the neonatal period after hospital admission. Detail history regarding gestational age, birth weight, place of birth, person conducting delivery, mood of delivery, problem at birth, residence, reasons of referral, vehicle during transport, condition of baby at arrival, time taken during transport and need for any resuscitation was recorded. Data were analyzed by using SPSS version 16.Result: Total 970 neonates were admitted during data collection period out of them 98(10.10%) died. Majority (58.16%) of the death occurred in neonate who was admitted before 72 hours of age having gestational age